Notes on the leafhopper genus Angustella Li (Hemiptera: Cicadellidae: Evacanthinae), with descriptions of four new species from China - Li, Yu-Jian; Li, Zi-Zhong (Zootaxa, 2011)
The paper deals with ten species of the genus Angustella Li, 1986 (Hemiptera: Cicadellidae: Evacanthinae), including four new species, Angustella panxianensis sp. nov., Angustella albida sp. nov., Angustella jinghongensis sp. nov. and Angustella nigrimargina sp. nov.